Pengaruh Beasiswa KIP Uang Kuliah Tunggal (UKT) Terhadap Prestasi Belajar Mahasiswa Program Studi Pendidikan Ekonomi Fakultas Keguruan Dan Ilmu Pendidikan Universitas Muhammadiyah Bengkulu - Erwani Yusuf; Wulan Sari (Universitas Dehasen Bengkulu, 2022)
This study aims to examine and determine whether there is an influence between UKT Scholarships on student achievement in the Economic Education Study Program, Faculty of Teacher Training and Education, University of Muhammadiyah Bengkulu. This study uses quantitative methods with data collection techniques using questionnaires. The sample used was 65 students who received UKT Scholarships. Data collection tools in this study are Observation which aims to observe the object to be examined directly, Questionnaire (Questionnaire) aims to obtain data on UKT Scholarships and Learning Achievements, Documentation aims to obtain information from the environment to be studied. The sampling technique used was Total Sampling. The data analysis technique used statistical package for social science (SPSS26) with the simple regression analysis method. The results showed that the UKT Scholarship (X) had a tcount of 3,740 with a Cronbach Alpha (researched result) of 73.5%, while learning achievement (Y) had a tcount of 6,687 with a Cronbach Alpha (sought result) of 86.2%, with the results of the ANOVA test Fcount 13,985. Thus, the effect of Single Tuition Scholarship (UKT) on Student Learning Achievement is 18.20%.